The UF/IFAS Assessment of Nonnative Plants in Florida’s Natural Areas: History, Purpose, and Use - Deah Lieurance; Stephen Luke Flory; Aimee L. Cooper; Doria R. Gordon; Alison M. Fox; Joan Dusky; Linda Tyson (EDIS)
Nonnative invasive plant species pose a significant threat to Florida’s natural areas. The UF/IFAS Assessment of Nonnative Plants in Florida’s Natural Areas (hereafter, UF/IFAS Assessment) uses literature-based risk assessment tools to predict the invasion risk of both nonnative species that occur in the state as well as species proposed for introduction. The UF/IFAS Assessment team has evaluated more than 770 species, including 97 species proposed for introduction or new uses. The team is actively identifying and evaluating potentially problematic nonnative species (and sub-specific or hybrid taxa). Recommendations and supporting information from the UF/IFAS Assessment can be found at http://plants.ifas.ufl.edu/assessment. This 6-page fact sheet was written by Deah Lieurance, S. Luke Flory, Aimee L. Cooper, Doria R. Gordon, Alison M. Fox, Joan Dusky, and Linda Tyson, and published by the UF Department of Agronomy, November 2013. http://edis.ifas.ufl.edu/ag376